Effect of Ionotropic Gelation Encapsulation on Iron Stability - Nansombat , Pheeranat; Jetsrisuparb, Kaewta (Srinakharinwirot University Engineering Journal, 2025)
This study focused on developing techniques to encapsulate ferrous sulfate (FeSO4) with sodium alginate (SA) by comparing two encapsulation methods: crosslinking SA using Fe2+ from FeSO4 as a crosslinker and immersion of SA beads in a FeSO4 solution. The aim was to enhance the stability of iron in a simulated gastric fluid at pH 1.2 and to release iron in a simulated intestinal fluid at pH 7.4. Analysis using Fourier Transform Infrared (FTIR) technique indicated successful binding of iron with alginate. Evaluation through UV-visible spectroscopy (UV-vis) and Atomic Absorption Spectroscopy (AAS) demonstrated that iron-alginate beads prepared by both encapsulation and immersion effectively reduced the release of Fe2+ and Fe3+ at pH 1.2 compared to unencapsulated FeSO4. In particular, the crosslinked beads released up to 30% more Fe2+ at pH 7.4 than immersed beads and unencapsulated FeSO4. This study demonstrated that using SA as an encapsulation material can reduce iron release in the gastric fluid, and crosslinking method resulted in Fe2+ that may be better absorbable in larger quantities in the intestine compared to soaking method and unencapsulated FeSO4.